Feminist Challenge to the Mainstream IR - Aydın, Gülşen (European Journal of Multidisciplinary Studies, 2016)
This study deals with the Feminist challenge to the Mainstream International Relations Discipline (IR) - rationalist theories, especially Realism - and the mainstream’s responses to this challenge. It addresses the issue in five steps. Firstly, it sheds light on how Feminism is related to International Relations. Secondly, it examines how Feminist IR theorists criticize the Mainstream IR due to its state-centric approach and argue that being obsessed with anarchic international system prevented analysis of social relations, including gender relations. Thirdly, the study addresses how Feminism exposes the gender biases in central terms such as power, autonomy, rationality, security, and state. Fourthly, it examines how Feminist writing on IR challenges the dichotomies of the Mainstream IR. Fifthly, the study examines how the Mainstream has responded to that challenge. The conclusion argues that although Feminist challenge to mainstream IR cannot be deemed successful in reconstructing IR, Feminism still enriches our understanding of global politics.